IImplementation of Balitar Islamic University of Blitar Legal Aid Services as a Form of MBKM - Eko, Yuliastuti; Novita, Setyoningrum; Gadung Putra, Panjalu (Fakultas Ilmu Sosial dan Politik, Universitas Negeri Surabaya, 2024)
This research aims to evaluate the implementation of Legal Aid Services (LBH) at the Bandung Islamic University (UNISBA) as part of the Merdeka Belajar Kampus Merdeka (MBKM) program. The method used is normative legal research, which involves analysis of relevant legislation and legal documents. The research results show that LBH UNISBA, through its partnership with the Blitar Religious Court and legal education activities in Ngeni Village, has succeeded in increasing access to justice for underprivileged communities and providing valuable practical experience for students. Students gain practical skills and an in-depth understanding of the law, while the public receives legal assistance and education that supports their legal awareness. This program strengthens the relevance of the curriculum and shows the synergy between higher education and the needs of society, in line with MBKM's goal of creating learning that is more connected to the real world. Keywords: legal aid; POSBAKU;, UNISBA